Obesity, Apolipoprotein E ε4, and Difficulties in Activities of Daily Living Among Older Adults: a 6-Year Follow-up Study. Issue 2 (13th October 2016) - Chen, Li-Jung; Steptoe, Andrew; Ku, Po-Wen
Abstract: Background: Obesity has been associated with increased physical limitations among older adults, although few studies have adjusted for important covariates. There is limited information about the relationship between apolipoprotein E (APOE) polymorphisms and physical limitations, and the findings have been inconsistent. Purpose: This study examined the longitudinal associations of obesity and APOE ε4 with difficulties in activities of daily living (ADLs) over a 6-year follow-up period controlling for multiple covariates. Methods: Data were analyzed from the Social Environment and Biomarkers of Aging Study (SEBAS) in Taiwan collected in 2000 and 2006, involving a cohort of 639 participants (mean age = 66). Body mass index (BMI) was used to define obesity at a baseline, and the APOE genotype was classified into an APOE ε4 carrier and non-carrier status. The combination of basic and instrumental activities of daily living (ADLs and IADLs) was used to define impaired ADLs. Results: APOE ε4 carriers had greater difficulties in combined ADLs (incident rate ratio; IRR = 1.87, 95 % CI = 1.40–2.51) than non-carriers. Obese but not overweight adults had greater difficulties in activities of daily living (IRR = 1.59, 95 % CI = 1.20–2.10) compared with the normal/underweight group. Obese older adults without APOE ε4 had greater subsequent difficulties in ADLs than non-obese non-carriers. Among APOE ε4 carriers, obesity was not a significant risk factor for the development of impaired ADLs in older adults, indicating an interaction between genotype and obesity. Conclusions: The interaction between genotype and obesity phenotype adds new information about the determinants of physical impairment.